Silence and the discoursive existence of God in Paul Ricoeur's hermeneuticsof religious discourse - Kerbs, Raúl (2000)
The paper analyzes the status of God's existence in Ricoeur's thought. This question emerges from the central character of language in religious experience and the reference to God in Ricoeur's hermeneutics.The A. examines whether in Ricoeur God has a discursive existence. S!nce this hypothesis presupposes that there is no place for silence at the word's origin,dueto God's existence being always related to language, this supposition is also examined. The A. wishes to support the idea that silence is always given in and by language. Consequently, the arguments favor God's discursive existence in the hermeneutics of Ricoeur's religious discourse.